EKOLOGI KONSERVASIF - Saputra, Jefri Andri (Jurnal Amanat Agung, 2022)
Abstract: The environmental pollution rate in Indonesia is still high in 2021. Some cases of pollution and forest fires in the mass media further confirm that the environmental crisis is still a struggle for the Indonesian people. The church as part of society must participate in solving this problem. To participate in efforts to build the church's ecological awareness, the author interprets the text of Colossians 1:19-20 through an ecological hermeneutic approach. Specifically, this text contains reconciliation from God to all things. The results of the author's interpretation indicate that reconciliation from God implies the restoration of creation towards its creation purpose. At the end of this paper, the author seeks for the church to make conservation ministry a part of ecclesiastical ministry to bridge the gap between the implications of God's reconciliation and and the current ecological facts. Keywords: Colossians 3, conservation, ecology, environmental crisis, reconciliation. Abstrak: Angka pencemaran lingkungan di Indonesia masih tergolong tinggi di tahun 2021. Beberapa kasus pencemaran dan kebakaran hutan di media massa mengindikasikan bahwa krisis lingkungan masih menjadi pergumulan masyarakat Indonesia. Gereja sebagai bagian dari masyarakat wajib berpartisipasi menyelesaikan masalah ini. Untuk berpartisipasi dalam usaha membangun kesadaran ekologis gereja, penulis menginterpretasi teks Kolose 1:19-20 melalui pendekatan hermeneutik ekologi. Secara spesifik teks ini memuat rekonsiliasi dari Allah kepada segala sesuatu. Hasil interpretasi penulis mengindikasikan bahwa rekonsiliasi dari Allah mengimplikasikan pemulihan ciptaan menuju tujuan penciptaannya. Di akhir tulisan ini, penulis mengupayakan agar gereja menjadikan pelayanan konservasif sebagai bagian dari pelayanan gerejawi untuk menjembatani kesenjangan antara implikasi rekonsilisasi Allah dengan fakta ekologis masa kini. Kata-kata Kunci: ekologi, Kolose 3, konservasi, krisis lingkungan, rekonsiliasi.